Determinants of digital banking adoption in the Kingdom of Saudi Arabia: A technology acceptance model approach - Hashem Abdullah Al-Nemer (Digital Business, 2022)
This study aims at investigating the determinants of digital banking adoption in the Kingdom of Saudi Arabia using the Technology Acceptance Model (TAM). The study is based on data from the 2017 Global Financial Inclusion Survey covering 1009 respondents, which has been analysed using simple analytical tools such as the chi-square test and logistics regression. About 51.5% of respondents reported adoption of digital banking in Saudi Arabia. The factor of trust in digital banking has been added to extend the Technology Acceptance Model (TAM) in predicting digital banking technology adoption. The two constructs of the Technology Acceptance Model (TAM) i.e. perceived ease of use (PEOU) and perceived usefulness (PU), show a significant and positive marginal effect on the adoption of digital banking, whereas trust indicates a negative and significant marginal impact with controlling effect of age and education of the consumers. This study provides valuable insights for financial institutions, consumers, business entities and researchers in promoting the digital banking system in Saudi Arabia.
Keywords: 650; Digital banking; Financial inclusion; Technology Acceptance Model (TAM); Saudi Arabia